PENGARUH KUALITAS PELAYANAN TERHADAP CITRA PERUSAHAAN (Studi Kasus Rumah Sakit Islam Ibnu Sina Pekanbaru) - Fanny Febriani; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is: (1) to find out and analyse the sevice quality (2) to find out and analyse the corporate iamge (3) to determine the influence of the service quality with corporate image in Ibnu Sina Islamic Hospital Pekanbaru. This research was conducted in the offices of Ibnu Sina Islamic Hospital Pekanbaru that is located on Melati Street. The research method used was quantitative. With the object of research is the Ibnu Sina Islamic Hospital Pekanbaru. With the method of data collection by means of questioner and interviews. Data analysis techniques using Simple Linear Regression analysis. With the result of the research there is service quality influences with corporate image in Ibnu Sina Islamic Hospital Pekanbaru of percent. Keywords: Service quality, corporate image.